Enhancing zinc and iron biofortification in mungbean (Vigna radiata L.) through various application method - Farooq, Hafsa; Ishtiaq, Rimsha; Babar, Haris; Faryad, Mohammad Hashim; Ameen, Maria; Abbas, Muhammad Taqqi; Mushtaq, Zain; Alasmari, Abdulrahman; Mondol, Md Sabir Ahmed; abdi, Gholamreza (Scientific reports, 2025)
Malnutrition is a problem in many developing economies where cereal crops are the main source of nutrition. Zinc and iron, important micronutrients, play an important role in the physiological and metabolic mechanisms of plants and humans. In this study a field experiment was conducted at the Agronomic Research Area, University of Agriculture, Faisalabad during zaid rabi season in February 2023 to check the impact of different application methods (seed priming, seed coating, soil application, and foliar application) of Zn and Fe on grain zinc and iron content and productivity in mungbean.. Results show that the plant growth parameters are significantly influenced by the concentration and application method of Zn and Fe. The highest plant height (cm), maximum number of branches and pods on plants were observed in foliar application of Zn and Fe combination treatment.. Post-harvest parameters, including biological yield, grain yield and 1000 seed weight were also positively influenced with highest biological yield (4536.27 kg ha −1 ) and grain yield (1927 kg ha −1 ) recorded under Zn foliar application. Physiological parameters such as chlorophyll content (SPAD value) and photosystem II Yield (Y(II)) were significantly improved with Zn and Fe treatment, particularly under foliar application. Biochemical analyses revealed that Zn and Fe significantly increase Zn and Fe content in grains with the highest value (36.77 and 63.44 ppm, respectively) observed under Zn foliar treatment. Overall, the foliar application was found most effective, in improving the yield and quality of mungbean. These findings highlight the efficacy of foliar application of Zn and Fe in enhancing mungbean growth, yield, and nutrient content, providing valuable insights for optimizing micronutrient management in mungbean cultivation.